The effect of Lactobacillus acidophilus,Streptococcus thermophilus, and Bifidobacterium longum probiotics on bilirubin levels of neonates with hyperbilirubinemia - Abbas, Pujiati; Mayangsari, Citra Primavita; Gunawan, Robby (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Hyperbilirubinemia, a common illness in newborns that can lead to hospital readmission, has been treated with blue light phototherapy. This treatment, either on its own or in combination with probiotics, has shown fast and significant decreases in bilirubin levels in the blood, helping to speed up the fading of jaundice. This study aims to examine the effects of combining phototherapy with probiotics containing Lactobacillus acidophilus, Streptococcus thermophilus, and Bifidobacterium longum on newborns with hyperbilirubinemia. The study was conducted at Sultan Agung Islamic Hospital (RSI Sultan Agung), Semarang, using a randomized controlled trial design. It included newborns who were hospitalized between August and November 2022. The control group was administered phototherapy, whereas the treatment group received both phototherapy and probiotics for 7 days. SPSS software analysis demonstrated a statistically significant reduction in average levels of total and indirect bilirubin in the intervention group (6.50 mg/dl and 7.20 mg/dl) compared to the control group (6.70 mg/dl and 7.48 mg/dl). These findings highlight the potential effectiveness of the combined approach in controlling hyperbilirubinemia. The study proposes using probiotics as a safe additional treatment for neonatal hyperbilirubinemia, showing that it is well-tolerated and safe for the participants. Although the combination of probiotics and phototherapy did not show a significant difference compared to phototherapy alone, it did result in a faster average decrease in hyperbilirubinemia. This could reduce the necessity for hospital readmissions to manage this condition. The findings underscore the potential of probiotics as a helpful supplement to established treatment methods for newborn hyperbilirubinemia.